2011
DOI: 10.1080/07481187.2011.553310
|View full text |Cite
|
Sign up to set email alerts
|

Meaning-Making Through Psychological Autopsy Interviews: The Value of Participating in Qualitative Research for Those Bereaved by Suicide

Abstract: Too often ethical boards delay or stop research projects with vulnerable populations, influenced by presumed rather than empirically documented vulnerability. The article investigates how participation is experienced by those bereaved by suicide. Experiences are divided into 3 groups: (a) overall positive (62%), (b) unproblematic (10%), and (c) positive and painful (28%). The positive experiences are linked to processes of meaning-making, gaining new insight, and a hope to help others. Objective factors concer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
60
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(76 citation statements)
references
References 25 publications
9
60
0
1
Order By: Relevance
“…Friends representing 30 of the 67 deceased (45%) filled out questionnaires. Based on previous research experience with populations bereaved by potentially traumatizing deaths, a careful and respectful approach was emphasized (Dyregrov, 2004;Dyregrov et al, 2011). because friends of both the youths and the few adults who were killed on Utøya were included.…”
Section: Purpose and Main Objectives Of The Studymentioning
confidence: 99%
“…Friends representing 30 of the 67 deceased (45%) filled out questionnaires. Based on previous research experience with populations bereaved by potentially traumatizing deaths, a careful and respectful approach was emphasized (Dyregrov, 2004;Dyregrov et al, 2011). because friends of both the youths and the few adults who were killed on Utøya were included.…”
Section: Purpose and Main Objectives Of The Studymentioning
confidence: 99%
“…In many cases, this opportunity to relay personal experiences has a cathartic effect on the participant, offering validity to their experience which may previously have been unrecognised (Dyregov 2004, Beck 2007Dyregov et al 2011). …”
Section: Qualitative Approachmentioning
confidence: 99%
“…Whilst there did not appear to be any qualitative studies exploring the impact of interviewing parents who had experienced a fatal child immersion, there have been qualitative studies which have explored parents' experiences of being involved in research following their child's death (Dyregov 2004;Hynson et al 2006;Taneja at al 2007;Dyregov et al 2011). These studies have suggested that the participants found the experience positive overall and suggested that, whilst the interviews were emotionally draining for many participants, they also had a beneficial effect, allowing the opportunity for the participant to vent their feelings and to help others by sharing their experiences and providing further insight into their situation.…”
Section: Qualitative Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…The participants were also made aware of the increased feelings of distress that may occur through being reminded of and talking about traumatizing life experiences in a research interview, and about the possibility of receiving follow-up grief counselling in their home town should such a need arise. However, suicide bereavement research has shown that talking about the suicide loss experience in research interviews is usually experienced as positive, due to the opportunity to further process the experience and to construct meaning from the loss in a supportive context (see for example Dyregrov et al 2011;Omerov et al 2014;Runesson and Beskow 1990). The Regional Ethical Review Board in Stockholm approved the first study (2009/1730-31/5) and the Regional Ethical Review Board in Linköping approved the second study (2012/380-31).…”
Section: Research Interviewsmentioning
confidence: 99%